Highly vibrationally excited O2 molecules in low-pressure inductively-coupled plasmas detected by high sensitivity ultra-broad-band optical absorption spectroscopy. (6th July 2015) - Foucher, Mickaël; Marinov, Daniil; Carbone, Emile; Chabert, Pascal; Booth, Jean-Paul
Abstract: Inductively-coupled plasmas in pure O2 (at pressures of 5–80 mTorr and radiofrequency power up to 500 W) were studied by optical absorption spectroscopy over the spectral range 200–450 nm, showing the presence of highly vibrationally excited O2 molecules (up to vʺ = 18) by Schumann–Runge band absorption. Analysis of the relative band intensities indicates a vibrational temperature up to 10, 000 K, but these hot molecules only represent a fraction of the total O2 density. By analysing the (11-0) band at higher spectral resolution the O2 rotational temperature was also determined, and was found to increase with both pressure and power, reaching 900 K at 80 mTorr 500 W. These measurements were achieved using a new high-sensitivity ultra-broad-band absorption spectroscopy setup, based on a laser-plasma light source, achromatic optics and an aberration-corrected spectrograph. This setup allows the measurement of weak broadband absorbances due to a baseline variability lower than 2   ×   10 −5 across a spectral range of 250 nm.